Ação da própolis sobre as proteínas do soro e aspectos hematológicos em Callithrix jaccus sp. submetidos ao estresse em cativeiro - Ferraz, Myrna de Campos [UNESP]; Matos, André Vicente Ruiz de [UNESP]; Moraes, Lívia Fagundes [UNESP]; Orsi, Ricardo de Oliveira [UNESP] (My University, 2011)
The present study aimed at evaluating the effect of propolis on serum proteins and hematological aspects in Callithrix sp marmosets kept in captivity and subjected to stress. Twenty-six Callithrix jacchus (white-tuffed-ear marmoset) and Callithrix penicillata (blacktuffed ear marmoset), aged between 8 and 18 months, males and females, were divided into three treatment groups: T1- fed during the whole experimental period on routine diet seven added of three grams of honey per individual; T2- routine diet added of three grams of honey and 2% crude propolis from daily diet, in relation to estimated daily consumption per individual; and T3- routine diet added of three grams of honey and 5% crude propolis from daily diet, in relation to estimated daily consumption per individual. Animals were fed during days with or without the addition of propolis (moment 1). After this period, they continued receiving the same diet scheme and were subjected to intrusive x resident stress for seven days (moment 2). The obtained results indicate that the addition of 5% propolis was harmful as regards serum proteins, decreasing this parameter significantly, suggesting that propolis concentration that has modulated the homeostasis of animals Thus, there is a great need for further studies employing varied stress periods, as well as different propolis administration times, concentrations and botanical sources in marmoset diet.

Este estudio tuvo como objetivo evaluar el efecto del propóleo en las proteínas del suero y los aspectos hematológicos en los “Tití” Callithrix sp en cautividad y sometidos a estrés. Se utilizaron 26 animales Callithrix jacchus (“Tití Común”) y Callithrix penicillata (“Tití de pinceles negro”), con edades comprendidas entre 8 y 18 meses, de ambos sexos, en tres tratamientos: T1- dieta de rutina, T2- dieta de rutina más 2% de propóleos en bruto y 3g de miel del individuo y T3- dieta de rutina más 5% de propóleos en bruto y 3g de miel por individuo (% en relación al consumo diario del individuo). Los animales fueron alimentados durante siete días con o sin la adición de propóleos (tiempo 1). Después de este período, los animales fueron sometidos a estrés intruso x residente durante siete días (tiempo 2), por un total de 14 días de tratamiento. La adición de propóleo al 5% redujo los niveles de proteínas del suero de manera significativa, lo que sugiere que la concentración de propóleos ha modulado la homeostasis de los animales. Sugerimos la realización de nuevos estudios con diferentes momentos de administración, período de estrés y concentraciones de propóleos, así como propóleos de diversos orígenes botánicos en la dieta de los “Titis”.

Este trabalho teve por objetivo avaliar o efeito da própolis sobre as proteínas do soro e aspectos hematológicos em saguis Callithrix sp mantidos em cativeiro e submetidos a estresse. Foram utilizados 26 animais da espécie Callithrix jacchus (sagui-de-tufo-branco) e Callithrix penicillata (sagui-de-tufo-preto), com idade entre 8 e 18 meses, de ambos os sexos, em três tratamentos: T1- dieta de rotina; T2- dieta de rotina acrescida de 2% de própolis bruta e 3 g de mel por indivíduo e T3- dieta de rotina acrescida de 5% de própolis bruta e 3 g de mel por indivíduo (% em relação ao consumo diário estimado por indivíduo). Os animais foram alimentados durante sete dias com ou sem o acréscimo de própolis (momento 1). Após este período, os animais foram submetidos ao estresse intruso x residente durante sete dias (momento 2), totalizando 14 dias de tratamento. A adição de 5% de própolis reduziu os níveis das proteínas do soro de forma significativa, sugerindo que a própolis nessa concentração tenha modulado a homeostase dos animais. Sugere-se a realização de novos estudos utilizando-se diferentes tempos de administração, período de estresse e concentrações de própolis, bem como própolis de distintas origens botânicas na dieta de saguis.
Propolis action on serum proteins and hematological aspects in marmosets (callitrhix sp) kept in captivity and subjected to stress
Efecto del propóleo en las proteínas del suero y los aspectos hematológicos en los “tití” (callithrix sp) en cautividad y sometidos a estrés
Keywords: propolis, marmosets, stress, animal welfare; propoleo, “Titis”, estrés, bien estar animal.; apiterápico, saguis, bem-estar animal, própolis